2017
DOI: 10.3390/rs9040379
|View full text |Cite
|
Sign up to set email alerts
|

Optical Backscattering Measured by Airborne Lidar and Underwater Glider

Abstract: Abstract:The optical backscattering from particles in the ocean is an important quantity that has been measured by remote sensing techniques and in situ instruments. In this paper, we compare estimates of this quantity from airborne lidar with those from an in situ instrument on an underwater glider. Both of these technologies allow much denser sampling of backscatter profiles than traditional ship surveys. We found a moderate correlation (R = 0.28, p < 10 −5 ), with differences that are partially explained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…Some previous studies on LiDAR at 532 nm reports χ (180 • ) was about 1.43 [35], while others report χ (180 • ) = 0.5 [33,34,36]. A new instrument for phase scattering function measurements is required, since most of the current methods cannot be extended to 180 • [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies on LiDAR at 532 nm reports χ (180 • ) was about 1.43 [35], while others report χ (180 • ) = 0.5 [33,34,36]. A new instrument for phase scattering function measurements is required, since most of the current methods cannot be extended to 180 • [37].…”
Section: Discussionmentioning
confidence: 99%
“…When the type of particles in the water does not change with depth, the Fernald method is better [16,17]. When changes in the depth profile of the optical properties are not too extreme, it is better to utilize the perturbation method [18][19][20]. For HSRL, the 2 properties can be retrieved independently [6,21].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, shipborne or airborne LiDAR has a wide range of oceanic applications, including bathymetry [2], measuring the optical properties of the water column [3][4][5], also for detecting plankton scattering layers [6][7][8], bubbles [9], internal waves [10], schools of fish [11] and so on. Recent breakthroughs have now demonstrated that plankton properties can be measured with a satellite LiDAR.…”
Section: Introductionmentioning
confidence: 99%
“…The max relative error percentage at both stations is within 8.3%, and their MREP is within 0.08%. The mean Lidar constant is K = 2.1026 × 10 10 (SR • m3 /s) for our Lidar system. The RMSE of lidar constant at S1 and S2 are 0.043 × 10 10 (SR • m 3 /s) and 0.033 × 10 10 (SR • m 3 /s), respectively.…”
mentioning
confidence: 97%